SIMBOL-SIMBOL DALAM IKLAN NIKE DI MEDIA YOUTUBE (ANALISIS SEMIOTIKA) - Zigit Dwi Dandi Pou; Jultje Aneke Juneke Rattu; Muh. Hasan Basri (CV Edujavare Publishing, 2026)
Nike symbolizes the Greek goddess of strength, speed, and victory, which is often reflected in the brand's visual narratives. This research, titled